Serving The Future: Factors Influencing Consumer Acceptance of Robotic Waiters in Restaurants - Adanan, Akmal; Azalea, Ras Natasha; Izzat, Mohd Adib; Darson, Mohamad Daim; Md Hasim, Ahmad Khairuman; Mohd Wasilan, Nadia Hanim Binti (Information Management and Business Review, 2024)
This research examines the factors influencing consumer acceptance of robotic waiters in restaurants. As the food service industry increasingly adopts robotic systems, it is essential to comprehend consumer approval for their effective integration. In this study, the Technology Acceptance Model (TAM) is utilized to investigate the key factors influencing consumer acceptance of robot waiters. It examines consumers’ evaluations of these robots’ usefulness and ease of use, as well as their attitudes and intentions. The findings illustrate the correlation between perceived usefulness, perceived ease of use, and attitude. Regression analysis highlights the significant roles of perceived ease of use and perceived usefulness in shaping attitudes toward technology, with the former having a more pronounced positive impact. However, anticipating future research into the complexities of user perception, particularly the negative correlation between perceived usefulness and attitude, is an exciting prospect for further investigation. This research enhances the understanding of consumer acceptance of robot waiters in restaurants and provides valuable insights for restaurant operators, policymakers, and other stakeholders. By addressing concerns related to technological adoption and customer preferences, this study guides the effective implementation of robot waiters in the restaurant industry, to improve operational efficiency and service quality.